Aerodynamic Analysis of Aircraft Wing - Triet, Nguyen Minh; Viet, Nguyen Ngoc; Thang, Pham Manh (VNU Journal of Science: Mathematics - Physics; Vol 31 No 2, 2015)
Aerodynamic problems in general are often difficult to solve by analytics analysis. Experimental or numerical simulation can be used to analyze these computational models. However, due to the large expenses required in the experimental method, the numerical method is more preferred. This paper presents the modeling and simulating processes of computational fluid dynamic (CFD) problem on a aircraft wing model, using typical section as NACA 2412 airfoil. This wing model might be chosen in the future experimental design. ANSYS Fluent is used to analyze the pressure and velocity distribution on the surface of wing. The lift and drag forces are also determined by ANSYS Structural. Additionally, the coefficients of lift and drag forces can be calculated through the data obtained when the relative velocity inlet between the airflow and airfoil changes from 0 to 50 m/s. The numerical results shown are compatible with those of the theory, thus suggesting a reliable alternative to predict the aerodynamic characteristics of the tested wing model in fabricating the Unmanned Aircraft Vehicles (UAVs). Keywords : Aerodynamic, airfoil, lift and drag, UAVs.